(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
In the present work density measurements are carried out on P-Cyanobenzylidene P- Nonyloxyaniline , liquid crystalline compound. The density is observed to drop with grow of temperature in mesogic phases expect in the vicity of stage transition it shows steep grow before it attains equilibrium value of the next part. Using density facts the various thermodynamic parameters like Moelwin Hughes parameter, Isochoric hotness coordinated of internal pressure, Sharma parameter Huggin’s parameter, Gruneisen parameter, etc. are assessed. The Bayer’s nonlinearity parameter is also estimated. All variables exhibit discontinuity at phase transformation. The outcome is discussed with instance to the literature facts accessible on number of samples.